Intervensi Menyikat Gigi Pada Anak Usia 6 – 12 Tahun Dengan Pendampingan Oleh Ibu Di Desa Keude Ulee Glee Kabupaten Pidie Jaya - Cut Ratna Keumala; Mardelita, Sisca; Liana, Intan; Andriani; Suryani, Linda; Nur, Arnela; Nurdin (Poltekkes Kemenkes Aceh, 2024)
Dental and oral hygiene can be achieved well by cleaning the teeth and mouth from food debris. The target activities of children aged 6-12 years in Keude Ulee Glee village, a total of 20 respondents are mothers. The first day's activities were in the form of health counseling on brushing techniques and maintenance of dental and oral health, starting with pretest and post test after counseling. Results of community service activities show an increase in knowledge before and after counseling. At the time of the demonstration of brushing, the child can do brushing his teeth properly and correctly, it is known that the plaque index before and after brushing teeth there is a difference (P<0.05). The results of this community service activity are expected to parents, especially mothers, to accompany their children to maintain dental and oral health as an effort to prevent caries.